DISPARITAS PUTUSAN HAKIM TINGKAT KASASI DALAM PERKARA NOMOR.1616 K/PID.SUS/2013 TENTANG TINDAK PIDANA KORUPSI - Nawarin P Situmeang; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Criminal disparity has become another problem in law enforcement in Indonesia. On one side of a different punishment / criminal disparity is a form of the judge's discretion in decisions, but on the other hand different penal / criminal disparity was also brought dissatisfaction to convict even society at large. The disparity in punishment for perpetrators of corruption made public distrust in judiciary, which is then manifested in the form of ignorance in the law enforcement community. The judge in this case that runs the institution that runs the court must memilii proper consideration in memetus case that this disparity is not a stumbling block for law enforcement. The purpose of this thesis, namely: first to determine the construction of thinking judges in criminal dropped on appeal in case No. 1616 K / Pid.Sus / 2013 on Corruption; the second; To know the advantages and disadvantages of the judge's ruling on appeal and the decision of the District Court in the decision No. 1616 K / Pid.Sus / 2013 on Corruption. This type of research can be classified types of normative legal research, descriptive research, a study that illustrates clearly and in detail about the construction of thinking judges in imposing punishment on Corruption, the source data used secondary data consisting of primary legal materials, legal materials secondary, and tertiary legal materials, techniques of data collection in this study with a literature study method, after the data is collected and analyzed to conclude From the results of research and discussion can be concluded that, first, in deciding this case the judges have used the juridical considerations and nonyuridis. The judges on Judex facti favors juridical considerations, where punishment is given only as a reply from the law, but on Judex juris judges have considered legally or nonyuridis decision making such decisions better reflect fairness. Second, Excess on appeal the judge's decision in the case No.1616 K / Pid.Sus / 2013 that the application of articles previously ignored by judges on Judex facti. As for the disadvantages, namely the existence of dissent of one judge Ad. Hoc additional penalty he did not agree on this point because the results are consistent with evidence of corruption in judex facti.Keywords: Diasparitas - Corruption - Verdict Judge.